Explaining Cooperation in the Council of the EU Before and After the Brexit Referendum - Johansson, Markus (2021)
This article focuses on the impact of the UK’s decision to leave the EU on cooperation within the Council of the EU. It does so by studying how cooperation between member states has changed from the period before the Brexit referendum to the period after. In the emerging literature on Brexit, it has been highlighted that member states that have been close partners to the UK will have to (and have started to) adjust their cooperation behaviour and form new alliances. While the structure of cooperation in the Council is often understood to be stable over time, suggesting that cooperation is mainly driven by structurally determined preferences that don’t easily change, a major event such as Brexit may force remaining member states to restructure their cooperation behaviour. Accordingly, it is expected and tested whether less structurally determined preferences have grown in importance for shaping patterns of cooperation in the immediate period following the Brexit referendum. Using survey data based on interviews with member state negotiators to the Council, asking about their network ties, compiled both in the period before and after Brexit referendum of 2016, it is shown that structurally determined preferences are important in both periods and that more volatile ideologically-based preferences on the EU integration dimension and GAL-TAN dimension have become important following the referendum. The article is informative both for those interested in the effects of Brexit on EU institutions, as well as those more generally interested in causes of cooperation patterns in the Council.